Some Results on the Extended Hypergeometric Matrix Functions and Related Functions - Mohamed Abdalla; Sahar Ahmed Idris; Ibrahim Mekawy (Journal of Mathematics)
In this article, we discuss certain properties for generalized gamma and Euler’s beta matrix functions and the generalized hypergeometric matrix functions. The current results for these functions include integral representations, transformation formula, recurrence relations, and integral transforms.